Isótopos de carbono e nitrogênio explicam diferenças em fontes de energia e segregação trófica de peixes em planícies de inundação Neotropicais. - Alves, Gustavo Henrique Zaia (2015)
Stable isotopes analyses have become a popular tool among ecologists. Carbon, nitrogen, hydrogen and sulfur stable isotopes are used to analyze many ecological attributes of populations, communities and ecosystems. The more commonly employed isotopes by freshwater ecologists are δ13C and δ15N, which are utilized as natural "markers" of biotic and abiotic molecules and are applied to reconstruct ecological processes or to trace ecological activities. Among the numerous freshwater ecosystems, river-floodplain systems are remarkable for being extremely complex ecosystems, with high biodiversity and high habitat heterogeneity, which makes these environments suitable to elucidate patterns and processes with stable isotopes. Thus, it is extremely important to recognize the factors that affect the variability of C and N isotopes, since the isotopic mapping of natural environments (isotopic landscape/isoscapes) has proven to be a great tool to elucidate migratory animal movement patterns, as well as the origin and fate of organic matter, including that of anthropogenic origin. Besides the isotopic landscapes, the elucidation of trophic niches through stable isotopes (e.g. isotopic niche) has also been widely used, especially when it comes to competition for food resources between native and non-native species. Therefore, the use of stable isotopes goes beyond the application of ecological theories, thus becoming an important tool for decision making when incorporated anthropogenic factors to the analysis. That being said, this thesis is divided into two themes: the first one assesses the factors that affect the variation of δ13C and δ15N of carbon sources in four Neotropical floodplains (Paraná, Pantanal, Amazon and Araguaia), highlighting local (limnological factors) and regional (basin identity) patterns. The second evaluates the trophic interactions of the population of an invasive fish species (Serrasalmus marginatus) and a native species (S. maculatus), through the analysis of stable isotopes in two floodplains (Pantanal, wherein the two species are native; and Paraná, where S. marginatus is non-native and potential competitor of S. maculatus). Due to the relatively greater heterogeneity within versus among systems in our study highlights that the spatial scale of sampling for control of baseline heterogeneity should be explicitly considered. As for the piranhas? trophic interactions, we found no evidence of niche overlap between the species, indicating that the coexistence of the species in the non-native co-occurrence environment is modulated by the niche segregation.